A novel mitochondrial membrane protein, Ohmm, limits fungal oxidative stress resistance and virulence in the insect fungal pathogen Beauveria bassiana. (27th December 2014) - He, Zhangjiang; Zhang, Suhong; Keyhani, Nemat O.; Song, Yulin; Huang, Shuaishuai; Pei, Yan; Zhang, Yongjun
Summary: The Hog1 mitogen‐activated protein (MAP) kinase regulates environmental stress responses and virulence in the entomopathogenic fungus B eauveria bassiana . To further characterize this pathway, we constructed a subtraction library enriched for genes regulated by Hog1. One targeted gene, encoding a novel membrane protein, O hmm (oxidative homeostasis membrane‐protein–mitochondria), was uniquely identified as being downregulated in the Δ H og1 background during growth under non‐stress and osmotic stress conditions, but upregulated under oxidative stress. Ohmm was an experimentally validated flavin‐binding protein and targeted to the mitochondria. Deletion of O hmm resulted in increased oxidative stress resistance, whereas overexpression caused an opposite phenotype. The Δ O hmm showed accumulation of reactive oxygen species with alterations in cell wall composition and compatible solute accumulation evident as compared with the wild type parent. Conidiation was reduced > 80%; however, conidia produced by the Δ O hmm strain germinated significantly faster than wild type cells. Insect bioassays using the greater wax moth revealed increased virulence for the Δ O hmm strain in both topical and intrahemocoel injection assays, indicating a negative effect of the presence of Ohmm with respect to pathogenesis. As predicted from our characterization, deletion of O hmm in a Δ Hog 1 background rescued its oxidative sensitivity phenotype, confirming that Ohmm acts downstream of the Hog1 MAP‐kinase.